In Vitro Antidiabetic and Antioxidant Potentials of Leaf and Stem Bark Extracts of a Mangrove Plant, Xylocarpus granatum. Issue 2 (2nd April 2016) - Das, Swagat Kumar; Samanta, Luna; Thatoi, Hrudayanath
ABSTRACT: Ethanol, methanol and aqueous leaf and stem bark extracts of Xylocarpus granatum (Meliaceae), a mangrove plant, were evaluated for their antidiabetic and antioxidant potentials. While the ethanol bark extracts exhibited the highest α-glucosidase inhibitory activity, the ethanol leaf extracts showed highest glucose uptake by yeast cells. The methanol and aqueous extracts of bark and methanol extracts of leaf showed highest antioxidant activities with the IC50 values of 41.40, 91.82 and 106.98 μg mL −1 for DPPH, superoxide and H2 O2 scavenging assays respectively. The ethanol bark extracts possess highest phenolic content with a value of 347.5 mg/g catechol equivalents.